Flim-Map: gene context based identification of functional modules in bacterial metabolic pathways - Bhatt, Vineet; Mohapatra, Anwesha; Anand, Swadha; Kuntal, Bhusan K.; Mande, Sharmila S. (Frontiers in microbiology, 2018)
Prediction of functional potential of bacteria can only be ascertained by the accurate annotation of its metabolic pathways. Homology based methods decipher metabolic gene content but ignore the fact that homologs of same protein can function in different pathways. Therefore, mere presence of all constituent genes in an organism is not sufficient to indicate a pathway. Contextual occurrence of genes belonging to a pathway on the bacterial genome can hence be exploited for an accurate estimation of functional potential of a bacterium. In this communication, we present a novel annotation resource to accurately identify pathway presence by using gene context. Our tool FLIM-MAP (Functionally Important Modules in bacterial Metabolic Pathways) predicts biologically relevant functional units called 'GCMs' (Gene Context based Modules) from a given metabolic reaction network. We benchmark the accuracy of our tool on amino acids and carbohydrate metabolism pathways.

Flim-MAP: gene context based identification of functional modules in bacterial metabolic pathways (vol 9, 2183, 2018) - Bhatt, Vineet; Mohapatra, Anwesha; Anand, Swadha; Kuntal, Bhusan K.; Mande, Sharmila S. (Frontiers in Microbiology, 2020)
Keywords: annotation; Bacteria; functional potential; gene context; genome; metabolic pathway

FunGeCo: a web-based tool for estimation of functional potential of bacterial genomes and microbiomes using gene context information - Anand, Swadha; Kuntal, Bhusan K.; Mohapatra, Anwesha; Bhatt, Vineet; Mande, Sharmila S. (2020)
Motivation: Functional potential of genomes and metagenomes which are inferred using homology-based methods are often subjected to certain limitations, especially for proteins with homologs which function in multiple pathways. Augmenting the homology information with genomic location of the constituent genes can significantly improve the accuracy of estimated functions. This can help in distinguishing cognate homolog belonging to a candidate pathway from its other homologs functional in different pathways. Results: In this article, we present a web-based analysis platform `FunGeCo' to enable gene-context-based functional inference for microbial genomes and metagenomes. It is expected to be a valuable resource and complement the existing tools for understanding the functional potential of microbes which reside in an environment.